2019
DOI: 10.21107/sml.v2i1.5521
|View full text |Cite
|
Sign up to set email alerts
|

Pola Pemanfataan Sumberdaya Laut Berbasis Kearifan Lokal Pada Masyarakat Wabula, di Kabupaten Buton

Abstract: <em>The research describes the patten of utilization of marine resources based on local wisdom in the Wabula community in Buton district. The data were collected by doing interwiews, observation, documentation, and study of literature. Then the data were analyzed descriptively and kualitatively. The results showed that in utilizing marine resources, Wabula community have a local wisdom called kaombo which is protected marine areas by the custom. When a marine area is designated as a kaombo a ban om the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
1
0
6
Order By: Relevance
“…Menurut Mustari, dkk. (2019), terdapat dua kawasan pembeda pada ombo/kaombo sebagai kawasan laut yang secara adat dilindungi yaitu kaombo awaktuu dan kaombo saumuru.…”
Section: Pembahasanunclassified
See 2 more Smart Citations
“…Menurut Mustari, dkk. (2019), terdapat dua kawasan pembeda pada ombo/kaombo sebagai kawasan laut yang secara adat dilindungi yaitu kaombo awaktuu dan kaombo saumuru.…”
Section: Pembahasanunclassified
“…Sebelum suatu kawasan laut ditetapkan sebagai kaombo awaktuu, maka sesuai tradisi masyarakat setempat akan diawali dengan melakukan musyawarah. Menurut Mustari, dkk. (2019), di dalam musyawarah akan dibahas beberapa hal diantaranya yaitu: (i) Menetapkan kawasan laut berupa batas-batas yag ditutup sementara atau menjadi kaombo untuk jangka waktu tertentu, (ii) Selama kawasan laut ditetapkan sebagai kaombo maka ditetapkan jenis-jenis biota laut dalam kawasan tersebut yang eksploitasi tidak boleh dilakukan, dan (iii) Dalam kaombo dimana tindakan deskruptif men-dapatkan sanksi.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Kaombo is a marine protected area established to ensure the sustainability of marine life in a sustainable manner. This utilization pattern is intended to avoid the sea as an open access area (Mustari et al 2019). Like the one in Webula, the islands in the Spermonde in Makassar also has local knowledge in conserving the sea, one of which is based on research conducted by Nurlia Ali et al in Therefore, if we explore more deeply about the local knowledge found in the Spermonde Islands, it can be seen based on the location of the island group.…”
Section: Local Knowledge Of Community In Spermonde Islandsmentioning
confidence: 99%
“…Wilayah kelola perairan berbasis masyarakat tidak hanya terikat dengan pengistilahan lokal tetapi juga melekat pada praktik pengelolaan wilayah yang dilakukan oleh kelompok/komunitas dengan tujuan perlindungan wilayah dan habitat, pemanfataan perikanan berkelanjutan, serta aktivitas lainnya yang mencakup upaya pengelolaan laut yang lestari. Beberapa wilayah kelola perairan/laut berbasis masyarakat di wilayah Indonesia diantaranya Panglima Laot di Aceh (Apriana, 2016;Puspita, 2017;Munar, 2018;Pranita, et al, 2021), Mulung di Nusa Tenggara Timur (Maruli, et al, 2021;Plaimo, et al, 2020;Wabang, et al, 2019) Awig-Awig di Bali dan Nusa Tenggara Barat (Asmara, et al, 2018;Putri & Citra, 2018;Wirasandi, et al, 2021), Sasi di Maluku (Gazali & Ruban, 2021;Soulisa, 2021;Badarudin, et al, 2021), serta Kaombo di Pulau Sulawesi (Estradivari, et al, 2022;Mustari & Manaf, 2019); Tenri, et al, 2019).…”
Section: Pendahuluanunclassified